Penerapan Metode Dekomposisi Sumudu untuk Menyelesaikan Persamaan Diferensial Biasa Orde Tiga Non Linear - rizky hamdanih; riry sriningsih (Journal of Mathematics UNP, 2019)
Abstract– This research discusses about the third order non linear ordinary differential equations. To solve the third order non linear ordinary differential equation we can using the Sumudu decomposition method.The Sumudu decomposition method is a combination of the Sumudu transform and the decomposition method which involving Adomian polynomial. This study aims to determine the completion steps and solutions has obtained from the application of the Sumudu decomposition method in to the third order non linear ordinary differential equations. The final solution obtained from the Sumudu decomposition method is a series solution.Keywords– Ordinary Differential Equations (ODE), Third Order Non Linear ODE, Sumudu.